Coffee in the City: An Analysis of the Hipster Culture’s Influence on Urban Regeneration in Inner City Johannesburg - Memela, Wetu (University of the Witwatersrand, Johannesburg, 2015)
The modern image of inner city Johannesburg is one that has undergone many transformations. These changes have been brought on by many different things, from the abolishment of political regimes to the rise of popular youth culture, such as the hipster culture today. Literature not only provides clear understandings but also debates, thoughts and questions of the hipster culture, urban regeneration and even the combination of the two. This research aims to understand the effect that the budding hipster culture has on inner city regeneration efforts in Johannesburg. Through the application of the Braamfontein case study, data collected in field work can be analysed through the literary understanding to paint an in-depth picture of not only the manifestation of the hipster culture in Braamfontein but also what affect their presence has on the district.
Planning Honours Report 2015, Wits University
Keywords: inner city, Johannebsurg, regeneration, culture, Braamfontein